PENGARUH KEDISIPLINAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK SELAMA PEMBELAJARAN HYBRID PADA MATA PELAJARAN EKONOMI - Rosari Nabila Denada; Dhiah Fitrayati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
requires student interest in learning so it is not surprising that student learning outcomes is relatively low. This is because students' mastery of economics subjects is still low. This study aims to determine the effect of discipline and learning motivation on learning outcomes in economics subjects at the time of hybrid learning in students of SMA Negeri 16 Surabaya. This type of research is quantitative research. Data collection techniques using questionnaires and documentation. The data collection tools using questionnaires. The results showed that the variables of discipline and learning motivation had a positive and significant effect both partially or simultaneously on learning outcomes. Based on the coefficient of determination, the variables of discipline and learning motivation contributed 29.1% to the learning outcomes of students. Suggestions from researchers to train the students to independently master the assigned tasks and to encourage the will to learn